Perlindungan Hak Kotak Kosong pada Pilkada Berdasarkan Undang-Undang Pilkada - Hardiansyah, Thoriq (Jurnal Konstitusi & Demokrasi, 2024)
Simultaneous elections in 2024 will be held as a whole, both legislative and executive. The implementation of Regional Head Elections, namely Governors, Mayors and Regents, has created its own phenomenon. This is due to the lack of political participation such as fat coalitions which result in the presence of the majority of single candidates in several regions dominated by incumbents. The opponent available on the ballot paper is an empty box. This certainly does not provide satisfaction to the community to be able to choose the candidate they will vote for so that a new phenomenon emerges, namely Empty Box Voters. In this study, the extent to which the state interprets substantive justice through the democratic party. The results of this study reveal that the Protection of Empty Box Voters and the Urgency of the presence of empty boxes can still be considered as the protection of Human Rights.